Guidance on the Development of Educational and Training Curricula WHO Regional Publications, European Series No 84 - Fitzpatrick, Martin (World Health Organization, 1999)
A practical guide to the development of curricula for the education and training of environmental health professionals. Prepared in consultation with educational institutes in a number of countries, the guide responds to both growing concern about environmental hazards and the need to ensure that professionals are adequately equipped with knowledge and skills. By recommending detailed model curricula for a range of professional categories, the book also aims to encourage the harmonization of int